FINANCIAL INCLUSION: AN EMPIRICAL STUDY ON BANKING HABITS OF THE PEOPLE OF THE RURAL AREA IN KOKRAJHAR DISTRICT OF BORO TERROTORIAL REGION OF ASSAM - Sanjay Karmakar; Nilanjana Deb (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
It is rightly said that a journey of thousand miles starts with one small step. Likewise, the Government of India has taken a slew of polices, measures and steps since several decades to counter and deal with various issues pertaining to financial exclusions and make the people of the country financially included to boost up the financial inclusion. In comparison to the mainland India, the North East India in general and Assam in particular are far legging behind in terms of Financial Inclusion according to the data released from time to time from various secondary sources. Moreover, the Boro Territorial Region of the Assam is far behind according to the data realised from CRISIL. Therefore, a need is felt to make a micro study in the region to find and unearth the status of the people of the region in terms financial inclusion viz a viz banking habit. Further in order to put the endeavour in this line, the statistical data has been presented with help of this article in order to furnish information regarding the aforesaid topic of discussion of this region.